Model‐based assisted migration of oracle forms applications: The overall process in an industrial setting. (12th May 2021) - Rodríguez, Cristo; Garcés, Kelly; Cabot, Jordi; Casallas, Rubby; Melo, Fabián; Escobar, Daniel; Salamanca, Alejandro
Abstract: The migration of software is an economically important niche since the daily operations of many business still rely on systems based on legacy technologies. Migration to more recent technologies comes with major technical and management challenges mainly related to knowledge‐loss issues on the specific technology but also on the architecture and design of the legacy. This article presents a method that addresses the reverse/forward engineering tasks as well as some management challenges such as the planning of the migration based on a better understanding of the system. The process relies on the use of models and transformations to create high‐level abstraction views of the legacy. A big challenge with the migration of certain legacy applications is that much of the business logic is inside triggers which are written in the PL/SQL language and scattered across the application layers. Therefore, developers need to know what they need to migrate and where it is. The main contribution of our work is that the abstractions allow developers to understand and plan the migration without the need of having a vast knowledge on the initial technology. Furthermore, our views help developers to decide about the structure and business logic they want to have in the target system. In this article, we describe the application of the method to the Oracle Forms case study. Nevertheless, the approach can be generalized to other technologies through new bridges that transform from said technologies to the abstract views. The article ends by reporting lessons learned from our experience.